1995
DOI: 10.1007/bf00040502
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase-like activity in Chrysanthemum leaf explants cultivated in vitro in relation to cell growth and hormone treatment

Abstract: In Chrysanthemum leaf explants cultivated in vitro the capacity to covalently link polyamines to protein substances exists. This plant enzyme activity shows some similarities with mammalian transglutaminases. In foliar explants cultured on a medium promoting bud or root formation increasing levels of transglutaminase-like activity occurred during the first days of culture when cell multiplication was rapid then the levels declined as the rate of cell division decreased and differentiation occurred. Undifferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Under our extraction protocol, the bound amine fraction was made up of amines covalently bound to proteins (Slocum 1991). High levels of binding of Put and Spd to proteins in actively dividing young tissues and lower binding in mature non‐dividing tissues of Chrysanthemum have been found (Aribaud et al 1995). The accumulation of bound Tya and PEA at 5/10°C and absence of these amines in the free forms, contrasting with the large accumulation of free Tya and absence of bound forms at 25°C, suggest an active endogenous binding in cold‐grown seedlings and not in 25°C‐grown seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Under our extraction protocol, the bound amine fraction was made up of amines covalently bound to proteins (Slocum 1991). High levels of binding of Put and Spd to proteins in actively dividing young tissues and lower binding in mature non‐dividing tissues of Chrysanthemum have been found (Aribaud et al 1995). The accumulation of bound Tya and PEA at 5/10°C and absence of these amines in the free forms, contrasting with the large accumulation of free Tya and absence of bound forms at 25°C, suggest an active endogenous binding in cold‐grown seedlings and not in 25°C‐grown seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the existence of endogenous transglutaminase activities in several plant tissues such as chloroplasts, mitochondria, cell walls, and cytoplasm in Arabidopsis (34) and in further plant sources (35)(36)(37)(38), for example, tobacco flower (Nicotiana tabacum), root and leaf tissue of the dicotyledonous pea (Pisum satiVum) and broad bean (Vicia faba) and the monocotyledonous wheat (Triticum aestiVum) and barley (Hordeum Vulgare) (20), and in lupin (39). Therefore, -(γ- glutamyl)lysine could be endogenously generated in products of these plants as a posttranslational modification of proteins.…”
Section: Verification Of the E-(γ-glutamyl)lysine Quantificationmentioning
confidence: 99%
“…Additionally, transglutaminase activities of maize calluses and chloroplasts, being involved in initial differentiation, were light-sensitive and affected by hormone deprivation (42). High transglutaminase activities have been ascribed to rapidly proliferating and growing organs, with decreasing activities occurring during maturity (38). On the other hand, -(γglutamyl)lysine could be generated in plant protein-containing products during extraction and processing (spray drying), since it is formed as a consequence of heat treatment in reactions independent of transglutaminase (16,43).…”
Section: Verification Of the E-(γ-glutamyl)lysine Quantificationmentioning
confidence: 99%
“…By the PPE extraction procedure, the proteins extracted are mainly of cytoplasmic origin. Depending on the authors and on the plant material used, the type of enzyme responsible for this amine binding was designated as TGase (Icekson and Apelbaum, 1987;Margosiak et al, 1990), TGase-like (Grandi et al, 1992;Aribaud et al, 1995), andDAO (Siepaı ¨o andMeunier, 1995). However, their potentialities regarding deamidation or protein cross-linking have never been described or investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In 1987, the binding of amines to proteins was observed in etiolated pea (Pisum sativum) apical meristems by Icekson and Apelbaum (1987) and was characterized as a Michaelis-Menten kinetic type enzyme, calcium independent. In recent studies, this activity was identified in tissues of H. tuberosus L. (Serafini-Fracassini et al, 1988), tobacco (Nicotiana tabacum) (Apelbaum et al, 1988), alfalfa (Medicago sativa L.) (Margosiak et al, 1990), spinach (Spinacia oleracea), broccoli (Brassica oleracea), silver beet (Beta vulgaris L.) (Signorini et al, 1991), lupine (Lupinus albus) (Pallavicini and Trentin, 1990), and Chrysanthemun (Aribaud et al, 1995). In all cases, this activity was referred to as TGase-like activity, although it was not strictly dependent on Ca 2+ ions like animal enzymes.…”
Section: Introductionmentioning
confidence: 98%